Reconceiving Impedance Matching and Mismatching to Mitigate Bias-Drift in Insertion Loss of Liquid Crystal Phase Delay Lines - Li, Jinfeng; Li, Haorong (Photonics Letters of Poland, 2025)
In microwave (MW), millimeter-wave (mmW), terahertz (THz), and optical beam-steering applications, amplitude imbalance among radiating elements in a phased array antenna feed system can become a point of significance in performance degradation, leading to beam squints, spatial errors, and uneven component lifespans. Higher power consumption in certain elements accelerates material hardening and aging, thereby increasing maintenance costs. This paper proposes a novel and cost-effective hardware approach to mitigate insertion loss imbalance in liquid crystal phase delay lines (LC-PDLs). The method compensates for internal losses without relying on feedback loops, thereby eliminating the need for conventional amplifiers or attenuators. Full Text: PDF References J. Li, "Challenges and Opportunities for Nematic Liquid Crystals in Radio Frequency and Beyond", Crystals 12, 5 (2022). CrossRef U. Chodorow, J. Parka, O. Chojnowska, "Liquid Crystal Materials in THz Technologies", Phot. Lett. Poland 4, 3 (2012). CrossRef B. Kress, "Optics and Photonics as a strong and resilient field for a successful career development", Phot. Lett. Poland 15, 2 (2023). CrossRef J. Li, D. Chu, "Liquid Crystal-Based Enclosed Coplanar Waveguide Phase Shifter for 54–66 GHz Applications", Crystals 9, 12 (2019). CrossRef J. Li, H. Li, "Optimal Dispatching of Microgrids with Development of Prosumers Sharing Energy Storage", Electronics 13, 3 (2024). CrossRef S. Bulja, D. Syahkal, R. James, S. Day, F. Fernández, "Novel Wideband Transition Between Coplanar Waveguide and Microstrip Line", IEEE Trans. Microw. Theory Tech. 58, 12 (2010). CrossRef J. Li, H. Li, "Modeling 0.3 THz Coaxial Single-Mode Phase Shifter Designs in Liquid Crystals with Constitutive Loss Quantifications", Crystals 14, 4 (2024). CrossRef D. Brown, "High-Speed, Hardware-in-the-Loop Phased Array Calibration with a Compact Antenna Test Range", 2024 IEEE International Symposium on Phased Array Systems and Technology (Boston, IEEE 2024). CrossRef